Protocol for an evaluation of the Designing Communities to Support Healthy Living in Aging Residents Study - Jodie A. Stearns; Hui Ren; John C. Spence; Hayford Avedzi; Karen K. Lee (Archives of Public Health, 2021)
Abstract Background In collaboration with building developers, the Housing for Health team is contributing to the design of community-based congregate living facilities to support healthy living in older adults. There may also be opportunities to improve the surrounding neighbourhoods by collaborating with the municipalities where the developments are located. We will evaluate whether one or more of these comprehensive interventions lead to changes in the perceived, microscale, and macroscale neighbourhood-built environment (BE) and amenities, and impacts on the physical activity (PA), healthy eating, and social connections of residents. In parallel, we will gather qualitative data to provide a more in-depth understanding of how the BE may facilitate or hinder resident’s healthy living outcomes. Methods This project employs a quasi-experimental pre-post design with at least one or more intervention and control sites. The quantitative BE evaluation will include pre- and post-intervention assessments of neighbourhood macroscale (e.g., layout of communities) and microscale (e.g., street details and characteristics) changes using Geographical Information Systems (GIS) and Microscale Audit Pedestrian Streetscapes (MAPS) audits, respectively. The quantitative resident evaluation will include self-report (i.e., surveys) and objective assessments (i.e., accelerometers, Global Positioning System [GPS]) of residents at baseline (3-6-months pre-move-in) and follow-up (3-6-months and 9-12-months post-move-in if possible). The qualitative resident-environment component will involve in-depth semi-structured interviews post-intervention with building residents, family members, and stakeholders involved in the design/development and/or operation of the intervention site(s). Participant observations will be completed in the building and neighbourhood environments of the intervention site(s). Discussion Findings will provide evidence on whether and how comprehensive changes to the BE and amenities of at least one congregate living facility and the surrounding neighbourhood can impact PA, healthy eating, and social connections of older adults. Successful intervention elements will be scaled up in future work. We will disseminate findings to a broad audience including the scientific community via peer-reviewed publications, conference presentations, and discussion panels; and the private, public, and not-for-profit sectors via reports, public presentations, and/or communications via our partners and their networks. Trial registration Protocol ID: 1819-HQ-000051. ClinicalTrials.gov ID: NCT05031273. Registered 29 June 2021 with ClinicalTrials.gov.